2013
DOI: 10.1136/annrheumdis-2012-202373
|View full text |Cite
|
Sign up to set email alerts
|

IL-17/Th17 mediated synovial inflammation is IL-22 independent

Abstract: These findings show that IL-17A/Th17 cell-mediated synovial inflammation is independent of IL-22 and Th22 cells. This implies that targeting IL-17A/Th17 cells, rather than IL-22/Th22 cells, should be the focus for treatment of T cell-mediated synovial inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 46 publications
5
44
0
Order By: Relevance
“…Nevertheless, an increased frequency of circulating Th17 cells has been reported in early RA, where Th17 cells were defined based on chemokine receptors [33]. Also, in line with our results, patients with very early RA have had increased serum levels of the Th17 polarizing cytokines IL-1b and -6 and of the Th17-derived cytokines IL-17A, IL-22, and IL-8 [34].…”
Section: Discussionsupporting
confidence: 90%
“…Nevertheless, an increased frequency of circulating Th17 cells has been reported in early RA, where Th17 cells were defined based on chemokine receptors [33]. Also, in line with our results, patients with very early RA have had increased serum levels of the Th17 polarizing cytokines IL-1b and -6 and of the Th17-derived cytokines IL-17A, IL-22, and IL-8 [34].…”
Section: Discussionsupporting
confidence: 90%
“…Cowan et al [85] found that both the Th17 response and IL-22 were differentially induced and observed a correlation between down regulation of IL-22 and progression of infection. These results correlate with those of van Hamburg et al [122], who investigated the effects of the Th17 response on IL-22 in rheumatoid arthritis. As with Cowan et al [85], the levels of IL-22 were negatively correlated with the progression of disease; an interaction primarily mediated by Th17.…”
Section: Modulation Of the Immune Responsesupporting
confidence: 90%
“…Number of Th17 cells is increased in peripheral blood of RA patients, and IL-17, which is greatly released in plasma and synovial fluid, has relevant roles mediating inflammation, microvascular function, and atherosclerosis. [37][38][39] On the contrary, although IL-17 levels strongly correlated with anti-CCP levels, in vitro treatment of normal lymphocytes with antiCCPs did not induce its expression. In this regard, it has been demonstrated that monocytes and fibroblasts from inflamed joints are able to induce the development of Th17 cells, 40,41 suggesting that interactions with other activated cells might be further required to induce the expression of IL17.…”
Section: Discussionmentioning
confidence: 88%